APLIKASI TEPUNG JINTAN HITAM (Nigella sativa) UNTUK PENCEGAHAN INFEKSI BAKTERI Streptococcus agalactiae PADA IKAN NILA (Oreochromis niloticus) - Raudhatus Sa'adah; Ade Dwi Sasanti; Ferdinand Hukama Taqwa (Universitas Sriwijaya, 2015)
ABSTRACT Streptococcosis is one of disease that attack nile tilapia (Oreochromis niloticus), which is caused by Streptococcus agalactiae. The aim of this research is to know effectivity of black cummin (Nigella sativa) to prevent S. agalactiae. This research was conducted on November-December 2014 in Laboratorium Budidaya Perairan, Laboratorium Dasar Perikanan and Laboratorium UPT. Klinik Kesehatan, Sriwijaya University. The design of this research used Complete Randomized Design (CRD) with five treatments and three replications were, fish fed commercial feed and infected, fish fed commercial feed and addition of black cummin 3.5%, 7%, 10.5% and 14% and infected. The result of this research showed the addition of black cummin to feed can prevented and increase immune system on nile tilapia to bacterial S. agalactie with dose 3.5%. The in vitro test showed inhibition zone diameter 1.75 cm and in vivo test showed hematocrite value 30%, survival rate 90% and increase weight and lenght growth on nile tilapia. Keywords : Streptococcosis, black cummin, nile tilapia